Moderate thinning enhances soil carbon-nitrogen cycling and microbial diversity in degraded mixed forests - Wang, Yu; Zhang, Baoshan; Yang, Xue; Xu, Fei (Frontiers in Microbiology, 2025)
IntroductionSoil carbon and nitrogen components play a crucial role in maintaining ecosystem functions and regulating global climate change in forest ecosystems. Thinning is an important forest management measure that significantly affects forest structure and biodiversity. However, the specific impacts of varying thinning intensities on soil carbon-nitrogen dynamics and microbial community structure remain unclear, warranting further investigation.MethodsIn this study, we applied a gradient of thinning intensities (10–35%) in a degraded mixed forest, combining field sampling, soil physicochemical measurements, and high-throughput sequencing to assess changes in soil carbon-nitrogen components and microbial communities. We used Mantel tests to quantify correlations between soil environmental factors and microbial community composition, variance partitioning analysis (VPA) to determine the relative contributions of carbon and nitrogen variables, and Boruta-based random forest modeling to identify the most important predictors of microbial variation. Mixed-effects models (controlling for elevation, slope, SI70) were used to test thinning effects on nitrogen fractions and C/N.ResultsBaseline (pre-treatment) soils exhibited high bacterial α-diversity but lower and more variable fungal diversity, with intermediate SOC and TN levels across plots. In contrast, fungal communities showed a simpler response, primarily influenced by the C/N ratio, dissolved organic carbon (DOC), and total nitrogen (TN). Mixed-effects models (controlling for elevation, slope, SI70) showed independent thinning effects on DON, MBN, NH4+-N, TN and C/N, but not on AN or NO3−-N. VPA showed that, for bacteria, carbon explained 26.86%, nitrogen 35.50%, and their interaction 29.04%; for fungi, 19.92, 38.68, and 34.87%, respectively—indicating nitrogen’s dominant role. The C/N ratio, TN, and NO3−-N had the highest explanatory power for thinning intensity, suggesting that nitrogen dynamics play a more significant role.DiscussionThe findings of this study improve the understanding of how forest management practices influence soil carbon-nitrogen, providing scientific evidence for the precise regulation of forest ecosystem functions and services, with significant implications for ecological management and climate regulation.